Effect of different orgaphosphates on the hepatic oxidative metabolism by mixed function oxidases in cattle - Larsen, Karen Elizabeth (2021)
Organophosphates (OPs) are widely used for crop protection in agriculture and for the control of ectoparasites in animal husbandry. The sustained use of these chemical compounds increases the risk of environmental contamination and/or alteration of different physiological cellular functions in farm animals. A number of OPs are substrates of hepatic mixed function oxidases, such as those belonging to the cytochrome P450 (CYP) and flavin-containing monooxygenase (FMO) families of enzymes. In addition, these xenobiotics may also affect enzyme function by induction or inhibition of their catalytic activities. This work aimed to evaluate in vitro the effect of the following OPs: chlorpyrifos (CPF), ethion (ETN), diazinon (DZN) and dichlorvos (DCV) on CYP- and FMO-dependent enzyme activities in cattle liver. Bovine (n=4) liver microsomes were incubated (10 min at 37°C in aerobiosis) in the absence (control assays) and in presence of each OP compound under study at 1, 10 and 100 µM (final concentrations). Five CYP- or FMO-dependent catalytic activities were assayed by spectrofluorimetric or HPLC methods: 7-ethoxyresorufin O-deethylase (EROD, for CYP1A1), methoxyresorufin O-demethylase (MROD, for CYP1A2), benzyloxyresorufin O-debenzylase (BROD, for CYP2B), testosterone 6-beta hydroxylase (for CYP3A) and benzydamine N-oxidase (for FMO). Only the CYP3A-dependent hepatic metabolism was significantly affected by the presence of ETN and DZN. ETN, at 10 µM and 100 µM, inhibited (p<0.01) testosterone 6-beta hydroxylase activity (76% and 81%, respectively) in cattle liver microsomes. Similar results were obtained in presence of equimolar concentrations of DZN (74% and 93% at 10 uM and 100 µM, respectively; p<0.01). Both ETN and DZN would potentially interfere with the pattern of the hepatic metabolism of relevant CYP3A substrates pharmacologically relevant in bovine medicine, such as tiamulin, macrolide antibiotics and the ionophore monensin.